Antioxidant enzyme activities and hormonal status in response to Cd stress in the wetland halophyte Kosteletzkya virginica under saline conditions. Issue 3 (30th July 2012) - Han, Rui‐Ming; Lefèvre, Isabelle; Albacete, Alfonso; Pérez‐Alfocea, Francisco; Barba‐Espín, Gregorio; Díaz‐Vivancos, Pedro; Quinet, Muriel; Ruan, Cheng‐Jiang; Hernández, José Antonio; Cantero‐Navarro, Elena; Lutts, Stanley
<x xml:space="preserve">Abstract</x> Salt marshes constitute major sinks for heavy metal accumulation but the precise impact of salinity on heavy metal toxicity for halophyte plant species remains largely unknown. Young seedlings of Kosteletzkya virginica were exposed during 3 weeks in nutrient solution to Cd 5 µM in the presence or absence of 50 mM NaCl. Cadmium (Cd) reduced growth and shoot water content and had major detrimental effect on maximum quantum efficiency (Fv/Fm), effective quantum yield of photosystem II (Y(II)) and electron transport rates (ETRs). Cd induced an oxidative stress in relation to an increase in O2− and H2O2 concentration and lead to a decrease in endogenous glutathione (GSH) and α‐tocopherol in the leaves. Cd not only increased leaf zeatin and zeatin riboside concentration but also increased the senescing compounds 1‐aminocyclopropane‐1‐carboxylic acid (ACC) and abscisic acid (ABA). Salinity reduced Cd accumulation already after 1 week of stress but was unable to restore shoot growth and thus did not induce any dilution effect. Salinity delayed the Cd‐induced leaf senescence: NaCl reduced the deleterious impact of Cd on photosynthesis apparatus through an improvement of Fv/Fm, Y(II) and ETR. Salt reduced oxidative stress in Cd‐treated plants through an increase in GSH, α‐tocopherol and ascorbic acid synthesis and an increase in glutathione reductase (EC 1.6.4.2) activity. Additional salt reduced ACC and ABA accumulation in Cd+NaCl‐treated leaves comparing to Cd alone. It is concluded that salinity affords efficient protection against Cd to the halophyte species K. virginica, in relation to an improved management of oxidative stress and hormonal status.